Effects of a telehealth programme using mobile data transmission on primary healthcare utilisation among children in Bamako, Mali. (September 2013) - Simonyan, David; Gagnon, Marie-Pierre; Duchesne, Thierry; Roos-Weil, Anne
Pesinet is a non-profit organisation which operates a microinsurance programme combined with a monitoring service in low-income countries to increase primary healthcare utilisation for children. We studied the association between enrolment in the Pesinet programme and changes in utilisation of health services. We conducted a prospective controlled study in Bamako (Mali) in children under five years old. Participants in the Pesinet service were recruited from a neighbourhood of Bamako (n = 91) and participants in the control group (usual care) came from two other neighbouring districts (n = 89). Eight questionnaires were completed at 2-week intervals for each child in the study. We performed logistic regression modelling to assess the effect of the Pesinet programme on health service utilisation, adjusting for confounding variables (age and socio-economic status). During the study, families reported 206 episodes of disease in the intervention group and 168 in the control group. Children from the intervention group had 85 medical consultations and those in the control group had 28. Based on the logistic regression model, there was increased utilisation of health care services among children enrolled in the Pesinet programme, with an adjusted Odds Ratio for medical consultations of 2.2. Membership of the Pesinet telehealth programme increased primary healthcare utilisation among children under five years old in Mali.